Implicit Theories of Intelligence and Achievement Goals: A Look at Students’ Intrinsic Motivation and Achievement in Mathematics - Liu, Woon Chia (Frontiers in Psychology, 2021)
The present research seeks to utilize Implicit Theories of Intelligence (mindsets) and Achievement Goal Theory to understand students’ intrinsic motivation and academic performance in mathematics in Singapore. 1201 lower-progress stream students (596 males, 580 females, 25 missing data), ages ranged from 13 to 17 years old (M = 14.68 years old, SD = .57) from 17 secondary schools in Singapore took part in the study. Using structural equation modelling, results confirmed hypotheses that incremental mindset predicted mastery-approach goal, and in turns, predicted intrinsic motivation and mathematics performance. Entity mindset predicted performance-approach and performance-avoidance goals. Performance-approach goal was positively linked to intrinsic motivation and mathematics performance, performance-avoidance goal, however, negatively predicted intrinsic motivation and mathematics performance. The model accounted for 35.9% of variance in intrinsic motivation and 13.8% in mathematics performance. These findings suggest that intrinsic motivation towards mathematics and achievement scores might be enhanced through interventions that focus on incremental mindset and mastery-approach goal. In addition, performance-approach goal may enhance intrinsic motivation and achievement as well, but to a lesser extent. Finally, the study adds to the literature done in the Asian context and lends support to the contention that culture may affect students’ mindsets and adoption of achievement goals, and their associated impact on motivation and achievement outcomes.